A systematic review on Chinese herbal treatment for radiotherapy-induced xerostomia in head and neck cancer patients. (February 2018) - Nik Nabil, Wan Najbah; Lim, Ren Jye; Chan, Si Yan; Lai, Nai Ming; Liew, Ai Ch'i
Abstract: Background: Over 80% of head and neck cancer patients suffer from radiotherapy-induced xerostomia (dry mouth). Xerostomia affects cancer patients' quality of life, and xerostomia sometimes persists throughout the patients' lifetime. This review aimed to evaluate the effectiveness and safety of Chinese herbs in relieving radiotherapy induced xerostomia. Methods: Systematic searches were conducted on 6 databases (English and Chinese). Studies published up till May 2017 were considered for inclusion. Results: A final 14 RCTs (total 994 head and neck cancer patients undergoing radiotherapy) compared Chinese herbs with no herbs, were included in analysis. Very low to moderate quality of evidence found Chinese herbal treatment may relief radiotherapy-induced xerostomia and other related complications (such as oral mucositis and loss of appetite) in head and neck cancer patients. Conclusion: There is limited evidence that Chinese herbal treatment may relief radiotherapy-induced xerostomia and other related complications in head and neck cancer patients. Highlights: A systematic review and meta-analysis of 14 randomised controlled trials. Chinese herbs were evaluated as an adjunct for head and neck cancer patients. Low-to-moderate quality evidence showing modest benefits in relieving xerostomia.